Planning and place in the city mapping place identity - Sepe, Marichela (Routledge, 2013)
"Under the influence of globalization, the centres of many cities in the industrialised world are losing their place identity, the set of cultural markers that define a city's uniqueness and make it instantly recognisable. A key task for planners and residents, working together, is to preserve that unique sense of place without making the city a parody of itself. Marichela Sepe explores the preservation, reconstruction and enhancement of cultural heritage and place identity. She outlines the history of the concept of placemaking, and sets out the range of different methods of analysis and assessment that are used to help pin down the nature of place identity. This book also uses the author's own survey-based method called PlaceMaker to detect elements that do not feature in traditional mapping and identifies appropriate planning interventions. Case studies investigate cities in Europe, North America and Asia, which demonstrate how surveys and interviews can be used to draw up an analytical map of place identity. This investigative work is a crucial step in identifying cultural elements which will influence what planning decisions should be taken the future. The maps aim to establish a dialogue with local residents and support planners and administrators in making sustainable changes. The case studies are amply illustrated with survey data sheets, photos, and coloured maps. Innovative and broad-based, Planning and Place in the City lays out an approach to the identification and preservation of place identity and cultural heritage suitable for students, academics and professionals alike. "--Provided by publisher.